2007
DOI: 10.1016/j.ahj.2007.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month randomized pilot study of black tea and cardiovascular risk factors

Abstract: In this randomized trial of black tea intake over 6 months among older adults with known cardiovascular risk factors, black tea did not appreciably influence any traditional or novel biomarkers of cardiovascular risk. Longer randomized trials are needed to verify the inverse association of tea with risk of cardiovascular disease seen in cohort studies and identify potential candidate mechanisms for such an association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 39 publications
0
38
0
1
Order By: Relevance
“…Allocation concealment was adequate in two studies [19,22]. Three studies adopted appropriate method (e.g.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Allocation concealment was adequate in two studies [19,22]. Three studies adopted appropriate method (e.g.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Therefore, 11 trials involved 411 adult participants were included in this metaanalysis. Six trials from 5 studies were conducted in healthy people [16,17,21,23,25] while the other five trials were performed in subjects with higher cardiovascular risk such as prediabetes or hypercholesterolemia [18e20, 22,24]. The sample size ranged from 15 to 77 with a median of 31.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Widlansky et al (49) observed, in patients with coronary artery disease, an increase in plasma catechins concentration after 4 weeks of daily ingestion of 900 ml black tea without any effect on CRP. In diabetic subjects, CRP and IL-6, were unaffected by green tea (900 ml) administration (50) as were fibrinogen, TNFa, intercellular adhesion molecule and vascular cell adhesion molecule after 6 months of daily consumption of black tea in diabetic subjects (51) .…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%